2017
DOI: 10.1111/apt.14334
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐centre audit of excess steroid use in 1176 patients with inflammatory bowel disease

Abstract: Steroid dependency or excess occurred in 14.9% of British IBD patients (in 7.1% potentially avoidable). We demonstrated positive effects of service configurations (IBD multi-disciplinary team, dedicated IBD clinics). Routine recording of steroid dependency or excess is feasible and should be considered a quality metric.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 23 publications
7
84
0
1
Order By: Relevance
“…[3][4][5][6][7] Our study is the largest study to examine this relationship and found that smoking status at diagnosis did not impact on the likelihood of corticosteroid exposure. 41 In a multivariable analysis we found no difference in corticosteroid dependency between never-smokers, smokers and ex-smokers. These findings are consistent with a recent meta-analysis that found no difference in flares of disease activity according to smoking status.…”
Section: Findings In Relation To Previous Studiesmentioning
confidence: 68%
“…[3][4][5][6][7] Our study is the largest study to examine this relationship and found that smoking status at diagnosis did not impact on the likelihood of corticosteroid exposure. 41 In a multivariable analysis we found no difference in corticosteroid dependency between never-smokers, smokers and ex-smokers. These findings are consistent with a recent meta-analysis that found no difference in flares of disease activity according to smoking status.…”
Section: Findings In Relation To Previous Studiesmentioning
confidence: 68%
“…Using a previously developed online assessment tool for steroid exposure in patients with IBD we prospectively collected data from IBD patients attending outpatient clinics over 3 months between April and July 2017. The participating sites worked with a standard operating procedure which required them to enrol all consecutive patients with IBD attending face to face clinics without patient selection beyond basic inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…To allow for comparison with the 2015 study we used the same definitions as detailed previously . In short we recorded steroid exposure (number of courses, length of the longest course, ability to taper, flares on or within 3 months of withdrawal) for the 12‐month period preceding the clinic visit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction Corticosteroid (CS) overuse and dependency has been highlighted as a key clinical outcome in the management of inflammatory bowel disease (IBD) in a recent national audit 1 . Whilst data regarding clinician prescribed CS is available 2 , little is known about the magnitude of self-prescribed CS amongst IBD patients, and we therefore aimed to investigate self-prescribing habits.…”
mentioning
confidence: 99%